Overweight and Obesity before, during and after Pregnancy - Stupin, J. H.; Arabin, B. (Geburtshilfe und Frauenheilkunde, 2014)
Overweight and obesity before conception as well as excessive weight gain during pregnancy are associated with endocrinological changes of mother and fetus. Insulin resistance physiologically increases during pregnancy, additional obesity further increases insulin resistance. In combination with reduced insulin secretion this leads to gestational diabetes which may develop into type-2-diabetes. The adipose tissue produces TNF-alpha, interleukins and leptin and upregulates these adipokines. Insulin resistance and obesity induce inflammatory processes and vascular dysfunction, which explains the increased rate of pregnancy-related hypertension and pre-eclampsia in obese pregnant women. Between 14 and 28 gestational weeks, the fetal adipose tissue is generated and the number of fat lobules is determined. Thereafter, an increase in adipose tissue is arranged by an enlargement of the lobules (hypertrophy), or even an increase in the number of fat cells (hyperplasia). Human and animal studies have shown that maternal obesity “programmes” the offspring for further obesity and chronic disease. Pregnant women, midwives, physicians and health care politicians should be better informed about prevention, pathophysiological mechanisms, and the burden for society caused by obesity before, during and after pregnancy.
Keywords: obesity; pregnancy; adipose tissue; perinatal programming; prevention